2002
DOI: 10.1074/jbc.m109980200
|View full text |Cite
|
Sign up to set email alerts
|

ABI5 Interacts with Abscisic Acid Signaling Effectors in Rice Protoplasts

Abstract: Abscisic acid (ABA) regulates seed maturation, germination, and adaptation of vegetative tissues to environmental stresses. The mechanisms of ABA action and the specificity conferred by signaling components in overlapping pathways are not completely understood. The ABI5 gene (ABA insensitive 5) of Arabidopsis encodes a basic leucine zipper factor required for ABA response in the seed and vegetative tissues. Using transient gene expression in rice protoplasts, we provide evidence for the functional interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 77 publications
3
37
0
Order By: Relevance
“…However, a synergistic effect has been observed with the bZIP and ABA, or with the bZIP, VP1, and ABA (Hobo et al, 1999;Gampala et al, 2002). Our data also agree with these observations.…”
Section: Discussionsupporting
confidence: 83%
“…However, a synergistic effect has been observed with the bZIP and ABA, or with the bZIP, VP1, and ABA (Hobo et al, 1999;Gampala et al, 2002). Our data also agree with these observations.…”
Section: Discussionsupporting
confidence: 83%
“…Observation of additional crossregulation among these ABI loci led to the suggestion that these transcription factors act combinatorially to regulate subsets of ABA-inducible and/or seed-specific genes. Subsequent studies demonstrated direct physical interactions between ABI5 and ABI3 or their rice (Oryza sativa) homologs in yeast (Hobo et al, 1999;Nakamura et al, 2001), as well as synergistic interactions between ABI5 and VP1 or their rice homologs in mediating ABAactivated gene expression in transient expression assays in plant protoplasts (Hobo et al, 1999;Gampala et al, 2002). ABI5 overexpression has been shown to resemble ABI3 overexpression in that it confers hypersensitivity to ABA inhibition of root growth and promotes slightly more efficient water retention (Parcy et al, 1994;Parcy and Giraudat, 1997;LopezMolina et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown by yeast two-hybrid screening that ABI5 interacts with ABI3 (40). Moreover, in transient assays, ABI5 has been demonstrated to trans-activate AtEM6 and phas promoters (38). The decrease in MAT and LEA gene expression (Fig.…”
Section: Pvalf-and Aba-mediated Activation Of the Phas Promotermentioning
confidence: 99%
“…ABI5, a b-zip class transcription factor, is a positive regulatory ABA signal effector (37) shown in transient assays to trans-activate phas promoter-driven GUS expression (38). It interacts with abscisic acid-response elements (39) and with ABI3 (40), and its debilitation leads to a severe reduction in LEA proteins (37).…”
Section: Dna Replication Arrest Affects the Aba-mediated Activationmentioning
confidence: 99%